Silicon Photonics – A Review Paper - Chhaya A. Bharambe,; Ankita Ravankar,; Namrata Kathale,; Nilesh M. Verulkar, (Journal of Electronic Design Engineering, 2016)
Silicon Photonics is outlined because the utilization of silicon-based materials for the generation, guide, management and detection of sunshine to speak over distances. Optical technology suffered from a name as an upscale answer, supported high price of hardware parts, as they are usually unreal victimization exotic materials that are dear for producing. These limitations prompted Intel to analysis the development of fiber-optic parts from alternative materials, like chemical element earned abundant attention in recent years attributable to the maturity of chemical element within the industry and its chance of monolithic integration of each photonic and electronic devices on one chip. It develops highvolume low price optical parts victimization standard CMOS method-the IC producing process used nowadays. The varied challenges also because the milestones within the development of chemical element Photonic area unit mentioned. the issue in fabricating optical devices like optical device supply, modulators, detectors etc. on chemical element for prime shift speeds that gives high information rates for communication links also because the solutions hints by the chemical element photonics analysis cluster at Intel area unit projected.